Centring Human Connections in the Education of Health Professionals - Melrose, Sherri; Park, Caroline; Perry, Beth (Athabasca University Press, 2021)
Many of today’s learning environments are dominated by technology or procedure-driven approaches that leave learners feeling alone and disconnected. The authors of Centring Human Connections in the Education of Health Professionals argue that educational processes in the health disciplines should model, integrate, and celebrate human connections because it is these connections that will foster the development of competent and caring health professionals.